Isolation, Synthesis and Medicinal Significance of Marine Pyridoacridine Alkaloids - Haider, Saqlain; Chittiboyina, Amar G.; Khan, Ikhlas A. (Current Organic Chemistry, 2019)
Pyridoacridine alkaloids, distributed in marine organisms have emerged as an important class of compounds due to their uniqure chemical architecture, diversity and medicinal significance. These alkaloids are reported to exhibit a wide array of biological activities like anti-cancer, anti-bacterial, ant-viral, anti-fungal and anti-parasitic activities. The present review highlights the isolation, synthesis and medicinal significance of this important class of pyridoacridine alkaloids.
Keywords: Pyridoacridine